Symposium 11: Expectations and Reality: Exploring the use of learning technologies across the disciplines - Hardy, Judy; Haywood, Denise; Bates, Simon; Paterson, Jessie; Rhind, Susan; Macleod, Hamish; Haywood, Jeff (Proceedings of the International Conference on Networked Learning, 2008)
The aim of the LEaD project is to undertake a study of first-year students from a variety of different entry routes and across a variety of subject areas at the University of Edinburgh. Its focus is on "critical moments"; more specifically, the involvement and impact of learning technology on learners' transition to University and how their use of learning technology changes as they progress through their first year.. The study includes a heterogeneous range of students from three academic disciplines: Physics, Veterinary Medicine and Divinity. Courses in these subject areas have an established e-learning presence and have begun to gain experience and understanding of how to embed Web2.0 tools such as weblogs, podcasts etc in support of the teaching, hence this is an ideal time to study the student perspective in parallel with these initiatives. The key objectives of the project are: To survey learners' expectations regarding the availability and use of e-learning at University. To observe how learners adapt and change their approaches to e-learning during their first year at University. To investigate to what extent learners use non-institutional / personal e-learning technologies to support their learning. To identify the key factors that influence learners' choices of e-learning strategies and how these are utilised. Teaching staff from each of the academic disciplines involved in the study are integral to the project team; their involvement is key to maintaining student engagement over the duration of the study. We have followed a mixed-mode approach, including a series of reflective student diaries recorded at key points over the academic year. together with collaborative and group discussion. In addition, since 1990 the University of Edinburgh has surveyed newly arriving undergraduates' experience and expectations of learning technologies and their use in teaching and learning by means of an online questionnaire. In our paper for the symposium we will discuss the tools and techniques used for data collection and will highlight emerging findings.